2017
DOI: 10.1002/ecy.1978
|View full text |Cite
|
Sign up to set email alerts
|

Parallel environmental factors drive variation in insect density and plant resistance in the native and invaded ranges

Abstract: Geographic variation in the traits of a species is shaped by variation in abiotic conditions, biotic interactions, and evolutionary history of its interactions with other species. We studied the geographic variation in the density of the lace bug, Corythucha marmorata, and the resistance of tall goldenrod Solidago altissima to the lace bug herbivory in their native range in the United States and invaded range in Japan. We conducted field surveys and reciprocal transplant experiments to examine what abiotic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…These results suggest that among‐population variation in tolerance to folivory may not be driven by herbivory pressure. Few studies have investigated broad geographic variation in tolerance, with one study showing the same latitudinal cline as reported herein (Lehndal and Ågren ) and the remaining studies showing no relationship between tolerance and latitude (Więski and Pennings , Prendeville et al , Sakata et al ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These results suggest that among‐population variation in tolerance to folivory may not be driven by herbivory pressure. Few studies have investigated broad geographic variation in tolerance, with one study showing the same latitudinal cline as reported herein (Lehndal and Ågren ) and the remaining studies showing no relationship between tolerance and latitude (Więski and Pennings , Prendeville et al , Sakata et al ).…”
Section: Discussionsupporting
confidence: 64%
“…To date, most investigations of the LHDH have focused solely on resistance mechanisms, largely ignoring other defense strategies such as plant tolerance (Anstett et al ). To our knowledge, only five studies have examined tolerance to herbivory along a latitudinal cline, with two finding support of the LHDH for resistance and the opposite pattern for tolerance (Lehndal and Ågren , b), and others finding no relationship between latitude and tolerance (Więski and Pennings , Prendeville et al , Sakata et al ). However, no studies have considered how tolerance in invasive species and co‐occurring native species might differ across a broad geographic range and contribute to invasion success.…”
Section: Introductionmentioning
confidence: 99%
“…From June to August 2013, we collected rhizome segments of S. altissima belonging to 10 genotypes from clumps at least 5 m apart from two populations in the USA (Minnesota, Kansas), and three populations in Japan (Saga, Shiga, Yamagata). Lace bugs were abundant on S. altissima in populations of Kansas, Saga, and Shiga, while they were absent or at low densities in populations of Minnesota and Yamagata (Sakata et al, , ). The rhizome segments were planted in a greenhouse at the Center for Ecological Research, Kyoto University, Japan and at the Research and Field Studies Center, University of Minnesota Duluth (Table ), followed by cultivation for two growing seasons to remove historical effects.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Uesugi and Kessler () found that Japanese S. altissima with low resistance to lace bugs showed lower production of leaf secondary metabolites such as diterpene acids, which may also affect resistance to other herbivorous insects. Diverse taxa of herbivorous insects were observed feeding on the plant in the USA, but very few taxa were observed in Japan (Sakata, Craig, Itami, Yamasaki, & Ohgushi, ). However, lace bug density was higher in Japan compared to the USA.…”
Section: Introductionmentioning
confidence: 99%
“…At each site, five quadrats were positioned in open ground and three quadrats in a narrow strip 25 m apart [27,28] to sample herbaceous plants. In each habitat, the relative foliage cover on each quadrat by visual(in percentage), number of individuals, and density and frequency of each plant species were quantitatively estimated using random quadrat methods [29]. A professional botanist helped identify the plants in the field.…”
Section: Data Collectionmentioning
confidence: 99%